1991
DOI: 10.1002/1520-6629(199110)19:4<283::aid-jcop2290190402>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Life events, chronic strain, and psychological distress: Longitudinal causal models

Abstract: This prospective study examines the causal relations among life events, chronic strain, and psychological distress. The influence of total number of life events; recent events; and undesirable, disruptive, and unanticipated events on marital strain and work/economic strain is assessed using latent variable structural equation modeling. It is hypothesized that chronic strain mediates the effects of life events on psychological distress. The data analyzed are from the first two waves of a prospective study on ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
2
16
0
1
Order By: Relevance
“…Moyle (16) found positive effects of time-1 distress on the perception of time-2 demands, whereas, in addition to normal causal effects, Garst et al (17) found effects from time-1 strain (depressive complaints, psychosomatic complaints, irritation, and worrying) on the perception of time-2 work stressors (job insecurity, time pressure, organizational problems, social stressors, and uncertainty). Three other longitudinal studies (18)(19)(20) found evidence for effects of prior depression on the perception of time-2 job characteristics. Finally, Taris (21) found effects of mental health status (depression, self-esteem, and general health) on the perception of job characteristics (eg, variety, autonomy, and job security).…”
Section: Prevalence Of Reversed or Reciprocal Effectsmentioning
confidence: 98%
“…Moyle (16) found positive effects of time-1 distress on the perception of time-2 demands, whereas, in addition to normal causal effects, Garst et al (17) found effects from time-1 strain (depressive complaints, psychosomatic complaints, irritation, and worrying) on the perception of time-2 work stressors (job insecurity, time pressure, organizational problems, social stressors, and uncertainty). Three other longitudinal studies (18)(19)(20) found evidence for effects of prior depression on the perception of time-2 job characteristics. Finally, Taris (21) found effects of mental health status (depression, self-esteem, and general health) on the perception of job characteristics (eg, variety, autonomy, and job security).…”
Section: Prevalence Of Reversed or Reciprocal Effectsmentioning
confidence: 98%
“…La survenue d'un événement stressant est associée dans les écrits scientifiques à la survenue de problèmes de santé mentale (Glickman et al, 1991). Il existerait un effet additif entre la tension au travail et l'événement stressant pour affecter la santé mentale des sujets de l'étude, ce qui occasionne des absences certifiées pour un problème de santé mentale.…”
Section: Discussionunclassified
“…Among employees on pay role, studies among an educated middle class sample (Aldwin & Revenson, 1986) and among skilled blue collar workers (Glickman, Tanaka & Chan, 1991) did show that people with poor mental health had a higher risk of running into financial problems and were also less likely to recover from them. However, their situation is different from that of self-employed individuals, and therefore results may not generalize to farmers.…”
Section: Financial Consequences Of Diminished Motivation and Deteriormentioning
confidence: 99%
“…Two longitudinal studies have addressed this issue, one among an educated middle class sample (Aldwin & Revenson, 1986) and one among skilled blue-collar workers (Glickman, et al, 1991). Results showed that individuals with poor mental health were more likely to experience financial hardship and were less likely to recover from it than those with better mental health.…”
Section: Impaired Health As a Cause Of Financial Problemsmentioning
confidence: 99%
See 1 more Smart Citation